The association between metabolic syndrome and vitiligo: a systematic review - Białczyk, Aleksandra; Kamińska, Barbara; Czajkowski, Rafał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2025)
Vitiligo is a chronic autoimmune disorder linked to systemic inflammation, oxidative stress, and metabolic dysregulation, including metabolic syndrome (MetS). This review examines the shared mechanisms underlying vitiligo and MetS, highlighting oxidative stress, pro-inflammatory cytokines, and lipid dysregulation as central contributors. A systematic analysis of 23 studies found association between vitiligo and MetS, though variations exist based on the disease type, severity, and duration. Emerging therapies, such as statins and thiazolidinediones demonstrate potential for managing vitiligo and its metabolic risks by targeting oxidative and inflammatory pathways. While animal and in vitro studies show promise, clinical outcomes are inconsistent, with safety concerns limiting systemic treatments.